Digoxin Is Associated With Increased All-cause Mortality in Patients With Atrial Fibrillation Regardless of Concomitant Heart Failure: A Meta-analysis - Wang, Zhi-Quan; Zhang, Rui; Chen, Man-Tian; Wang, Qun-Shan; Zhang, Yi; Huang, Xiao-Hong; Wang, Jun; Yan, Jian-Hua; Li, Yi-Gang (Journal of cardiovascular pharmacology, 2015)
For decades, digoxin has been widely used to control ventricular rate in atrial fibrillation (AF). However, it remains controversial as to whether digoxin is associated with increased mortality in AF. In this study, we searched relevant studies that were published before December 1, 2014, in PubMed, EMBASE, and the Cochrane central databases. We systematically reviewed the references and performed a meta-analysis of 8 carefully selected studies with 302,738 patients who were included for the final analysis. It was shown that digoxin use was associated with increased risk of all-cause mortality in AF overall [hazard ratio (HR) = 1.375, 95% confidence intervals (CI), 1.201-1.574, P = 0.0001]. Subgroup analysis further revealed that digoxin was associated with increased all-cause mortality in patients with AF, which was complicated by heart failure (HF) (HR = 1.201, CI, 1.074- 1.344, P = 0.001), and in those subjects without HF (HR = 1.172, CI, 1.148-1.198, P = 0.0001). Sensitivity analyses found results to be robust. Our findings indicated that digoxin use was associated with significantly increased all-cause mortality in patients with AF regardless of concomitant HF. We suggest that digoxin should not be preferentially used over other rate control medications in AF.